3rd Biennial Prague : young artists from Central Europe. - Malá, Olga; Srp, Karel; 3rd Biennial Prague, 1999 (Praha : Prague City Gallery, 1999)
Bakos, Gábor ; Lakner, Antal ; Weber, Imre ; Binder, Erik ; Blazo, Cyril ; Brueckl, Rosa ; Schmoll, Gregor ; Gerhes, Gábor ; Hajdu, Kinga ; Jaros, Piotr ; Jermolaewa, Anna ; Kadlecek, Michal ; Kamera skura ; Kuris, Martin ; Lanyi, Drahomira ; Lishakova, Galina ; Muntean, Markus ; Rosenblum, Adi ; Nagy, Kriszta ; Nemes, Csaba ; Pechoucek, Michal ; Rajkowska, Joanna ; Rukschcio, Fiona ; Szépfalvi, Agnes ; Simlova, Stepanka ; Soltys, Dusan ; Vukoje, Maja ; Witek, Anita ; Zasadni, Wojciech ; Zebrowska, Alicja ; Zmijewski, Artur
ind. tent., gr. tent. per kunstenaar
Engels & Tsjechisch
3rd Biennial Prague : young artists from Central Europe, The House of the Stone Bell, Prague City Gallery, Praha, 22 October 1999 - 9 January 2000
boek
Keywords: Centraal-Europa